Paediatric drugs trials in China - Wei Zhao; Wei Guo; Guo-Xiang Hao; Xiao-Xiao Yuan; Xi-Yu Quan; Xue-Jie Qi; Tian-You Wang (BMJ Publishing Group, 2020)
Objective Clinical trials of children's drugs are of great significance to rational drug use in children. However, paediatric drugs trials in China are facing complex challenges. At present, the investigation data on registration status of paediatric drug trials in China are still relatively lacking, and relevant research is urgently needed.Methods The advanced retrieval function is used to retrieve clinical trials data in the Clinical Trial.gov and Chinese Clinical Trial Registry databases in 22 April 2019. Fifteen key items were analysed to describe trial characteristics, including: registration number, study start date (year), mode of funding, type of disease, medicine type, research stage, research design, sample size, number of experimental groups, placebo group, blind method, implementation centre, child specific, newborn specific and participant age.Results A total of 1388 clinical trials of paediatric drugs conducted in China were registered. The number of paediatric drug trials grew steadily over time, from less than 20 per year before 2005 to more than 100 per year after 2012. Most clinical trials were postmarketing (n=800, 57.6%), single-centre (n=1045, 75.3%), intervention studies (n=1161, 83.6%) without blinded methods (1169, 84.2%) and funded by non-profit organisations (n=838, 60.4%). The number of clinical trials for antineoplastic agents (n=254, 18.3%), anti-infectives (n=156, 11.2%) and vaccines (n=154, 11.1%) is the largest.Conclusion Paediatric drug trials in China made a significant progress in recent years. Innovative method and trial design optimisation should be encouraged to accelerate paediatric clinical research. Pharmaceutical companies need to be further stimulated to carry out more high-quality paediatric clinical trials with support of paediatric drug legislation.